Arytenoid cartilage chondroma. Issue 5 (October 2015) - Lee, Dong Hoon; Kim, Jo Heon; Yoon, Tae Mi; Lee, Joon Kyoo; Lim, Sang Chul
Abstract: Arytenoid chondroma is an extremely rare benign cartilaginous tumor. We report a case of a patient with arytenoid chondroma initially mimicking laryngopharyngeal reflux. Clinicians should consider the possibility of the arytenoid chondroma in the differential diagnosis of patients with vocal cord palsy, or arytenoid swelling caused by laryngopharyngeal reflux.